Working out a rational model of Lithuanian construction industry development - Zavadskas, Edmundas Kazimieras; Kaklauskas, Artūras (Journal of Business Economics and Management, 2005)
The research aim was to develop a model for determining rational micro and macro‐level factors for the construction industry in Lithuania by undertaking a complex analysis of environment affecting it and to give recommendations on the increase of its competitive ability. In modelling and forecasting future perspectives and the main development trends of the Lithuanian construction industry, it is possible to be prepared for effective changes in environment. The analysis of construction industry in developed countries and Lithuania can allow identify areas where the situation in Lithuania is comparable, partly comparable with or quite different from the level attained by the above foreign countries. The data of this analysis can be used in identifying construction industry development trends in developed countries as well as providing some recommendations for Lithuania. Proposed model would be designed to give insights into the factors which affect the construction and which require effective management. In order to demonstrate the application of the above research to developing rational model of Lithuanian construction industry some recommendations for improving situation in Lithuanian construction are presented.First published online: 14 Oct 2010